Reorienting Vulnerability: An Analysis of Deborah Levy’s Hot Milk - Flores-Quesada, María Magdalena (Universidad de Valladolid, 2021)
This article seeks to challenge the traditionally negative connotations of the notion of vulnerability. I propose to approach the concept in dialogue with Giorgio Agamben’s idea of potentiality to demonstrate that both potential and vulnerability can be regarded as transforming and empowering characteristics for the subject. I analyse the protagonist of Deborah Levy’s Hot Milk(2016) under this light to show how a subject can use vulnerability as the fulcrum of freedom and agency, particularly in the context of a problematic mother-daughter relationship. I suggest that understanding vulnerability as potentiality allows a reorientation of our conception of the victim or the vulnerable as subjects in potential power.

Este artículo cuestiona las connotaciones tradicionalmente negativas de la noción de vulnerabilidad. Se aborda el concepto en relación con la idea de potencialidad de Giorgio Agamben para demostrar que tanto la potencialidad como la vulnerabilidad pueden considerarse características transformadoras y empoderantes para el sujeto. En este contexto, se analiza a la protagonista deHot Milk,de Deborah Levy (2016),para mostrar cómo un sujeto puede utilizar la vulnerabilidad como eje hacia la libertad y la voluntad, particularmente enel marcode una relación problemática entre madre e hija. Se concluye que entender la vulnerabilidad como potencialidad permite reorientar nuestra concepción de la víctima o del vulnerable como sujetos con un poder potencial.
Reorientando la vulnerabilidad: un análisis de Hot Milk de Deborah Levy
Keywords: Levy, Deborah (1959-) - Crítica e interpretación; Ficción moderna y contemporánea; Deborah Levy; Hot Milk; British fiction; Giorgio Agamben; mother-daughter; Vulnerability; Potentiality; Contemporary fiction